PROGRAM MBKM ASISTENSI MENGAJAR SEBAGAI UPAYA MENINGKATKAN KOMPETENSI MAHASISWA UNIVERSITAS ISLAM LAMONGAN - Kirana, Asmidhea Vienanusa; Yada, Kholifatin Maha; Hartanti, Olivia Febrian; Mumtahana, Lusia (Universitas Islam Lamongan, 2024)
Students are required to have adequate competence so that when the time comes to enter society, students can participate in improving the quality of human resources as well as helping to understand society in terms of knowledge and practice. Qualitative data processing methods and data collection techniques using a series of interviews, observations and field visits. The results of this study show that Teaching Assistance activities can actually improve the competence of Unisla students in various ways, including: creating fun and more colorful classroom conditions using more diverse learning methods and media, being able to provide counseling to students and being able to arrange teaching hours. optimally.